2020
DOI: 10.1523/jneurosci.1926-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a Neuronal Drp1 Activator Protects against Cerebral Ischemia

Abstract: Mitochondrial fission catalyzed by dynamin-related protein 1 (Drp1) is necessary for mitochondrial biogenesis and maintenance of healthy mitochondria. However, excessive fission has been associated with multiple neurodegenerative disorders, and we recently reported that mice with smaller mitochondria are sensitized to ischemic stroke injury. Although pharmacological Drp1 inhibition has been put forward as neuroprotective, the specificity and mechanism of the inhibitor used is controversial. Here, we provide ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…However, inhibiting DRP1 remains an ongoing challenge. Indeed, it has been found that the deletion of a neuron-specific DRP1 activator, Bβ2 (a mitochondria-localized protein phosphatase 2A regulatory subunit), in vivo ameliorated excessive stroke damage [ 216 ]. Interestingly, DRP1 also participates in processes other than mitochondrial fission in vascular tissues following ischemic injury, such as ischemia-induced autophagy, apoptosis, and metabolic pathways [ 217 ].…”
Section: Mito-recovery: Regaining Mitochondrial Homeostasis In Is mentioning
confidence: 99%
“…However, inhibiting DRP1 remains an ongoing challenge. Indeed, it has been found that the deletion of a neuron-specific DRP1 activator, Bβ2 (a mitochondria-localized protein phosphatase 2A regulatory subunit), in vivo ameliorated excessive stroke damage [ 216 ]. Interestingly, DRP1 also participates in processes other than mitochondrial fission in vascular tissues following ischemic injury, such as ischemia-induced autophagy, apoptosis, and metabolic pathways [ 217 ].…”
Section: Mito-recovery: Regaining Mitochondrial Homeostasis In Is mentioning
confidence: 99%
“…The mechanism by which DRP1 interacts with Zip1-MCU to allow mitochondrial zinc influx is unclear. Furthermore, whether excess zinc interferes with this mitochondrial surveillance mechanism has not yet been demonstrated in neurons, although it is an intriguing topic of future study due to the extent that DRP1 activation and mitophagy have been implicated in the pathology of various neurodegenerative diseases [ 235 ], such as AD [ 234 , 248 ], PD [ 249 , 250 , 251 ], HD [ 252 , 253 ], ALS [ 254 ], and ischemia [ 255 , 256 ].…”
Section: Zinc and Mitochondrial Dynamicsmentioning
confidence: 99%
“…Dynamin-related protein 1 (Drp1) is a key protein that regulates mitochondrial fission after brain ischemia 19 . Many studies have shown that downregulating Drp1 can induce neuroprotection after stroke 20,21 . To explore the potential molecular mechanisms of CB1 receptor activation, in the present study, we used oxygen-glucose deprivation/reoxygenation (OGD/R) and middle cerebral artery occlusion (MCAO) in vitro and in vivo, respectively, as brain IRI models and examined whether the CB1 agonist ACEA protects ischemic brain tissue via the CB1-Drp1 pathway by inhibiting mitochondrial fission.…”
Section: Introductionmentioning
confidence: 99%